The Impact Of PDCA Cycle Implementation On Nursing Management In Hospitals: A Systematic Literature Review - Hapsari, Niky Isa; Chalidyanto, Djazuly (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Effective nursing management is a crucial factor in improving the quality of healthcare services in hospitals. One approach that can be applied in nursing management is the PDCA (Plan-Do-Check-Act) cycle, which aims to enhance efficiency and effectiveness in the care process. This article aims to analyze the impact of PDCA cycle implementation on nursing management in hospitals. The method used in this study is a systematic literature review with a PICOS approach, utilizing databases from PubMed and ScienceDirect. Out of the 26 articles obtained based on the keywords “PDCA Cycle” and “nursing management”, 8 articles met the inclusion criteria: (1) implementation of the PDCA method in nursing management; (2) a quantitative study with an intervention; (3) articles published no earlier than 2020; and (4) international publications. The results indicate that the implementation of the PDCA cycle on nursing management has a positive impact on both patients and nurses. For patients, outcomes include reduced complications and infection rates, shorter hospital stays, fewer side effects, and improved satisfaction. For nurses, benefits include enhanced compliance with procedures, better infection control practices, reduced workload and errors, and increased professional competency and safety. Therefore, the PDCA cycle can be considered an effective approach to improving the quality of nursing management.